Silver Nanoparticle-Coated Ethyl Cellulose Inhibits Tumor Necrosis Factor-α of Breast Cancer Cells - Abdellatif AAH; Alsharidah M; Al Rugaie O; Tawfeek HM; Tolba NS (Dove Medical Press, 2021)
Ahmed AH Abdellatif,1,2 Mansour Alsharidah,3 Osamah Al Rugaie,4 Hesham M Tawfeek,5 Nahla Sameh Tolba6 1Department of Pharmaceutics, College of Pharmacy, Qassim University, Buraydah, 51452, Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Al-Azhar University, Assiut, 71524, Egypt; 3Department of Physiology, College of Medicine, Qassim University, Buraydah, 51452, Saudi Arabia; 4Department of Basic Medical Sciences, College of Medicine and Medical Sciences, Qassim University, Unaizah, AlQassim, 51911, Saudi Arabia; 5Department of Industrial Pharmacy, Faculty of Pharmacy, Assiut University, Assiut, 71526, Egypt; 6Department of Pharmaceutics, Faculty of Pharmacy, Sadat City University, Sadat City, EgyptCorrespondence: Ahmed AH AbdellatifDepartment of Pharmaceutics, College of Pharmacy, Qassim University, Buraydah, 51452, Saudi ArabiaEmail a.abdellatif@qu.edu.saIntroduction: Cancer is one of the leading causes of death worldwide. In many cases, cancer is related to the elevated expression of a significant cytokine known as tumor necrosis factor-α (TNF-α). Breast cancer in particular is linked to increased proliferation of tumor cells, high incidence of malignancies, more metastases, and generally poor prognosis for the patient. The research sought to assess the effect of silver nanoparticles reduced with ethyl cellulose polymer (AgNPs-EC) on TNF-α expression in MCF-7 human breast cancer cells.Methods: The AgNPs-EC were produced using the green synthesis reduction method, and their formation was proofed via UV–VIS spectroscopy. Furthermore, AgNPs-EC were characterized for their size, charge, morphology, Ag ion release, and stability. The MCF-7 cells were treated with AgNPs-EC. Then, the expression of TNF-α genes was determined through PCR in real time, and protein expression was studied using ELISA.Results: The AgNPs-EC were spherical with an average size of 150± 5.1 nm and a zeta-potential of − 41.4± 0.98 mV. AgNPs-EC had an inhibitory effect on cytokine mRNA and protein expression levels, which suggests that they could be used safely in the fight against cancer. AgNPs-EC cytotoxicity was also found to be non-toxic to MCF-7.Conclusion: Our data determined AgNPs-EC as a novel inhibitor of TNF-α production. These results are promising for developing novel therapeutic approaches for the future treatment of cancer with safe materials.Keywords: silver nanoparticles, tumor necrosis factor-α, ethyl cellulose, MCF-7 cells